2022
DOI: 10.33005/ijdasea.v2i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of System Dynamics to Increase Successful Utilization of E-Commerce with Marketing and Innovation Capability in MSMEs

Abstract: Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economic development of many cities around the world. The role of MSMEs can encourage equitable economic development which is one of the main pillars of the ASEAN Economic Community (AEC). But unfortunately, there are still many people who do not know how to market a new product and have a large market potential by using internet technology. The ongoing COVID-19 pandemic is causing changes in individual habits which also has the opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous studies have revealed the benefits of transforming MSMEs through innovation and technology. Research by Fitri et al, (2022) showed that using e-commerce can improve market access and sales of MSMEs [2]. Maheshwari et al, (2021) found that implementing business management software helped improve operational efficiency and inventory management [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed the benefits of transforming MSMEs through innovation and technology. Research by Fitri et al, (2022) showed that using e-commerce can improve market access and sales of MSMEs [2]. Maheshwari et al, (2021) found that implementing business management software helped improve operational efficiency and inventory management [3].…”
Section: Introductionmentioning
confidence: 99%